The potential of marketing communications to protect social workers in times of crisis. (3rd October 2022) - Pervan, Simon; Rayne, Daniel; Bove, Liliana
ABSTRACT: Socially stigmatized service workers (SSWs) like probation officers, social workers, and even aged care workers are often subject to negative media scrutiny when a crisis occurs, leading to public outrage and subsequent high attrition rates. The primary focus of this study is to examine the potential for marketing communication to generate a state of empathic concern amongst the public towards SSWs because an empathic public is less likely to want to punish, despite media calls to do so. A case is presented for the use of marketing communication explained through the lens of narrative execution and the general theory of emotion. Using a content analysis of public service announcements from representative bodies of social workers, in the US, UK and Australia we find little evidence of strategic intent to use narrative format or elicit empathic concern. A call and direction for further research is made in light of this finding.